Pengaruh Media Pembelajaran Monopoli Terhadap Hasil Belajar Matematika Peserta Didik Kelas IV SDN Wringinharjo 02 - Nabilahsari, Putri; Isnaati, Pebri; Riyadi, M. Ilham Rahmani (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of this study is to determine the effect of using monopoly learning media on the mathematics learning outcomes of fourth-grade students at SDN Wringinharjo 02. This study uses a quantitative approach with a pre-experimental research type. The chosen research design is one group pre-test and post-test, with data collection instruments in the form of test questions given before and after the treatment. Based on the results of the study entitled "The Use of Monopoly Learning Media on the Mathematics Learning Outcomes of Fourth-Grade Students at SDN Wringinharjo 02," it was found that the monopoly learning media has a significant effect. This is evident from the average post-test percentage score reaching 83.25%. The normality test results showed a significance value of 0.320 for the pre-test and 0.072 for the post-test, while the homogeneity test showed a value of 0.074. In addition, the hypothesis analysis using the Paired Samples Test at a 5% significance level produced a value of 0.000 < 0.05, so it can be concluded that Ho is rejected and Ha is accepted. In other words, there is an effect of the Monopoly learning media on the improvement of mathematics learning outcomes of fourth-grade students at SDN Wringinharjo 02.